Memristors and nonequilibrium stochastic multistable systems. (November 2022) - Spagnolo, B.; Dubkov, A.A.; Carollo, A.; Valenti, D.
Abstract: The main aim of this special issue is to report the recent advances and new trends in memristors and nonequilibrium stochastic multistable systems, both theoretically and experimentally, within an interdisciplinary context. In particular, memristors are multistable systems whose switching dynamics is a stochastic process, which can be controlled by internal and external noise sources, unveiling the constructive role of random fluctuations. Furthermore, the use of memristors as memory elements in neuromorphic systems with noise-assisted persistence of memory states, chaotic dynamics, metastable chaos and chaos synchronization, new stochastic nonlinear models, noise-induced phenomena such as stochastic resonance, noise enhanced stability and phase transitions phenomena in memristors will be illustrated in the contributions of this special issue.